2017
DOI: 10.1007/s10548-017-0609-4
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Robustness of Frequency-Domain Connectivity Measures to Finite Data Length

Abstract: In this work we use numerical simulation to investigate how the temporal length of the data affects the reliability of the estimates of brain connectivity from EEG time-series. We assume that the neural sources follow a stable MultiVariate AutoRegressive model, and consider three connectivity metrics: imaginary part of coherency (IC), generalized partial directed coherence (gPDC) and frequency-domain granger causality (fGC). In order to assess the statistical significance of the estimated values, we use the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…Recent comparative studies have assessed causal effects with various causality measures, using also significance tests for each causal effect [ 14 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Some studies concentrated on the comparison of direct and indirect causality measures [ 46 , 52 ], whereas other studies focused on specific types of causality measures, e.g., frequency domain measures [ 53 , 54 , 55 , 56 ], or different significance tests for a causality measure [ 57 , 58 , 59 ]. These studies are done on specific real data types, mostly from brain, which limits the generalization of the conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Recent comparative studies have assessed causal effects with various causality measures, using also significance tests for each causal effect [ 14 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Some studies concentrated on the comparison of direct and indirect causality measures [ 46 , 52 ], whereas other studies focused on specific types of causality measures, e.g., frequency domain measures [ 53 , 54 , 55 , 56 ], or different significance tests for a causality measure [ 57 , 58 , 59 ]. These studies are done on specific real data types, mostly from brain, which limits the generalization of the conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…A similar modelling framework was adopted in (Sommariva et al 2017) to investigate how the temporal length of the data affects the reliability of the estimates of brain connectivity in frequency domain from EEG time-series. Also in this study it was shown that even exact knowledge of the source time courses is not sufficient to provide reliable estimates of the connectivity when the number of samples gets small.…”
mentioning
confidence: 99%
“…In practice, data length is always finite, and the reliability of these methods is impacted by the overall number of available data time points. This issue has been discussed in simulated data for linear coupling methods (e.g., Sommariva et al, 2017), while for cross-frequency coupling methods this is still to be explicitly investigated. Moreover, to date several evidences have been provided concerning the changes of functional connectivity patterns across different time-scales (Breakspears et al, 2004).…”
Section: Discussionmentioning
confidence: 99%